Flexible urban transportation - Gifford, Jonathan Lewis (Elsevier Science, 2003)
Flexible Urban Transportation is a sweeping reassessment of American highway and transit policy. For the last half-century, this policy has been fixated on planning, designing and constructing the Interstate highway system, and then coping with the creative destruction it wrought. Aggressive construction of the Interstate divided and destroyed urban communities, and sparked a furious backlash, the "Freeway Revolt". The Interstate also facilitated widespread suburbanization of housing, retail and employment, which in turn gave rise to the tightly integrated, flexible supply chains cha